(untitled) (Praxis Educativa, 2024)
From a qualitative approach, this paper aims to analyse the articulation and communication policies of the provincial educational administration of Cambiemos (2015-2019) with the actors of the educational community of Buenos Aires. Specifically, we intend to investigate the place occupied by families as actors of the educational community in the political agenda of Cambiemos, in a scenario of dispute with trade unions on the forms of regulation of education. The Buenos Aires education government of Cambiemos found in families, as actors of the educational community, a potential ally to reorient the educational administration from the supply of the State towards the demand of the beneficiaries of the policies. At the same time, families were presented as a strategic management actor for the construction of new territorial alliances that could displace and weaken the historical weight of other organised actors in the community, such as teachers’ unions.